Legal Protection of Equal Rights to Pension Guarantees for Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) in the Perspective of Maslahah Mursalah - Fitriani, Wama; Cholidi, Cholidi; Yazwardi, Yazwardi (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The inequality of legal protection regarding pension benefit rights between Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) remains a crucial issue in the governance of the Indonesian State Civil Apparatus (ASN). Although the State Civil Apparatus Law outlines material and non-material entitlements for ASN in general, each category of personnel does not yet receive equal access to pension security. This disparity creates problems of fairness, legal certainty, and state accountability in protecting ASN as public service providers. This study aims to explore the legal protection of equal pension rights for PNS and PPPK through a constitutional law review and the application of the maslahah mursalah principle. The research employed a normative juridical method by examining statutory regulations, legal doctrines, court decisions, and relevant literature. The findings reveal that existing pension regulations do not ensure equal legal protection between PNS and PPPK, resulting in welfare disparities within the ASN system. Through the perspective of maslahah mursalah, pension benefits for all ASN constitute a form of public interest that promotes humane treatment after years of service, provides psychological security regarding future planning, and reduces the risk of socio-economic vulnerability in old age. The implications of this study highlight the urgency for regulatory harmonization of pension schemes to ensure equality between PNS and PPPK, reflecting distributive justice, legal protection, and improved governance of the ASN system in Indonesia. [Ketimpangan perlindungan hukum terkait kesetaraan hak jaminan pensiun antara Pegawai Negeri Sipil (PNS) dan Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) masih menjadi persoalan krusial dalam tata kelola Aparatur Sipil Negara (ASN) di Indonesia. Walaupun Undang-Undang Aparatur Sipil Negara telah menetapkan hak materiel dan nonmateriel bagi ASN secara umum, masing-masing kategori pegawai belum sepenuhnya memperoleh jaminan hak yang setara, khususnya dalam aspek jaminan pensiun. Kondisi ini menimbulkan problem keadilan, kepastian hukum, serta konsistensi perlindungan negara terhadap ASN sebagai pelaksana layanan publik. Penelitian ini bertujuan untuk mengkaji perlindungan hukum terhadap kesetaraan hak jaminan pensiun bagi PNS dan PPPK melalui tinjauan hukum tata negara dan pendekatan prinsip maslahah mursalah. Metode penelitian yang digunakan adalah penelitian yuridis normatif dengan menelaah peraturan perundang-undangan, doktrin hukum, putusan, dan literatur relevan. Hasil penelitian menunjukkan bahwa pengaturan jaminan pensiun belum memberikan kesetaraan perlindungan hukum antara PNS dan PPPK, sehingga menimbulkan disparitas kesejahteraan bagi ASN. Melalui analisis konsep maslahah mursalah, jaminan pensiun bagi seluruh ASN menjadi bagian dari kemaslahatan publik karena memberikan perlakuan manusiawi setelah masa pengabdian, menciptakan rasa aman psikologis terhadap perencanaan masa depan, serta mengurangi risiko kerentanan sosial dan ekonomi pada usia lanjut. Implikasi penelitian ini menegaskan urgensi harmonisasi regulasi jaminan pensiun yang setara bagi PNS dan PPPK sebagai wujud keadilan distributif, perlindungan hukum, dan penyempurnaan tata kelola ASN di Indonesia.]